The Effect of Using Illustrated Crossword Media to Improve the English Reading Ability of Intellectually Disabled Students - Kartika Kartika; Pamuji Pamuji; Asri Wijiastuti (Jurnal ORTOPEDAGOGIA, 2025)
The ability possessed by mentally retarded students in reading English is still in the low category compared to students in general. In their learning, mentally retarded students need help in the form of media to make it easier for students to understand the material explained by the teacher. One of the media that can be used in learning is a pictorial crossword puzzle. Besides being able to facilitate understanding, crossword puzzles can also make learning activities more fun. This study aims to determine the reading ability of mentally retarded students in learning English before and after the application of pictorial crossword puzzles. This study uses a research method in the form of a quantitative method using a Pre Experimental Design approach in the form of One Group Pretest-Posttest Design. For the data collection process using a test instrument in the form of questions. This research was conducted using the subject of students with mental retardation class VII SMPLB . The results showed that with the use of pictorial crossword puzzles, students' English reading skills increased based on the difference in scores obtained at the pretest and posttest. The value obtained during the posttest is greater than the value obtained at the pretest. The conclusion in this study is that the use of crossword puzzles has an influence in improving students' English reading skills. This can be seen through the results of the Wilcoxon test which shows that Asymp. Sig. (2-tailed) < 0.05.